Polarographic and voltammetric determination of trace amounts of 2-nitronaphthalene - Pecková, Karolina; Barek, Jirí; Moreira, Josino Costa; Zima, Jirí (Analytical and bioanalytical chemistry, 2005)
The polarographic behaviour of 2-nitronaphthalene was investigated by DC tast polarography (DCTP) and differential pulse polarography (DPP), both at a dropping mercury electrode, and differential pulse voltammetry and adsorptive stripping voltammetry, both at a hanging mercury drop electrode. Optimum conditions have been found for the determination of 2-nitronaphthalene by the given methods in the concentration ranges of 2 x 10(-6) - 1 x 10(-4), 2 x 10(-7) - 1 x 10(-4), 1 x 10(-8) - 1 x 10(-4) and 2 x 10(-9) - 1 x 10(-8) M, respectively. Practical applicability of these techniques was demonstrated by the determination of 2-nitronaphthalene in drinking and river water after its preliminary separation and preconcentration using liquid-liquid and solid-phase extraction with limits of determination of 3 x 10(-10) M (drinking water) and 3 x 10(-9) M (river water).
Keywords: Sensitivity and Specificity; Naphthalenes; Electrochemistry; elektrochemie; senzitivita a specificita; naftaleny